18F-FDG PET/CT IN DIFFERENTIATING EQUIVOCAL CT LESIONS IN PATIENT WITH COLORECTAL CANCER - Spirov, Goran; Beshliev, Simon; Matveeva, Niki; Spirov, Vasilcho; Ugrinska, Ana (Journal of Morphological Sciences, 2022)
Imaging is vital in the follow-up strategy of patients with colorectal cancer. Computed tomography is widely accepted as a method of choice, but further work up is required when equivocal findings are present. The objective of this study was to investigate the potential of positron emission tomography (PET)/computed tomography (CT) as a problem-solving tool of dubious CT findings in patients with colorectal cancer (CRC) in the follow-up period. This was a retrospective review of thirty-two patients referred for 18F-fluorodeoxyglucose (FDG) PET/CT imaging due to suspicion of recurrent disease solely based on CT exam. The diagnosis of a malignancy lesion was based on intensity of the lesion, location, shape, size, as well as CT findings.  There was a follow-up period of at least six months after the PET/CT examination. The most common site of detected lesions that could not be characterized by CT were the lungs (13/32; 40.5%), followed by liver (8/32, 25%) and lymph nodes (5/32, 15.6%). Additionally, lesions were reported at adrenal gland, spleen, peritoneum, ovary and at surgical site. In almost half of the patients (15/32; 46.8%) lesions were detected by PET/CT and characterized as disease recurrence. Metastases at additional site were detected in five patients (6/15, 40%).  In the follow-up period recurrent disease was detected in two patients (2/32, 6.2%) with negative PET/CT findings. Only one person had a false positive finding. The overall positive and negative predictive value of FDG-PET/CT was 93.3% and 84.6% respectively. PET/CT offers a high overall positive and negative predictive value in distinguishing CRC metastasis. Furthermore, it exceeds CT performance in detecting extrahepatic recurrent disease.                                   Keywords : PET scan, CT scan, imaging, colorectal cancer.   https://doi.org/10.55302/JMS2251001s